Stimulus-secretion coupling in L cells and factors affecting secretion of glucagon-like peptide 1 - Cyranka, M (2023)
Glucagon-like peptide 1 (GLP-1) is a hormone released from gut endocrine L cells in response to the arrival of nutrients and plays an important role in regulating glucose homeostasis. However, factors and pathways modulating the stimulus-secretion coupling of GLP-1 are not fully understood. Our group previously reported a significant increase in GLP-1 plasma levels from an Abcc5 knockout (Abcc5-/-) mouse model, but the mechanism responsible for this effect remains unknown. Additionally, Abcc5-/- mice generated by other groups have reported an accumulation of various glutamate-conjugated compounds in the brain and other tissues, which could be responsible for driving the altered metabolic phenotype of the Abcc5-/- mice and also potentially affecting their behaviour.